Pengembangan Business Model Canvas pada Destinasi Wisata Pantai di Wilayah Pesisir Balikpapan Timur - Mochammad Henfi Abdul Khoir (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
The development project of the National Capital City (IKN) located not far from Balikpapan City also influences travel patterns and the need for the tourism sector, which directly increases the number of tourists coming to this city. In this context, Balikpapan Timur District, located in the eastern coastal area of ​​Balikpapan City, is one of the areas that has great potential to be developed as a strategic tourist destination, with increasingly rapid growth in demand from immigrant people and tourists. The purpose of this study is to formulate the development of a business process for coastal tourist attractions in Balikpapan Timur District using the Business Model Canvas approach. The research method used is descriptive qualitative because it aims to obtain a clear picture related to the main problems being studied. The results of the study recommend the development of a Business Model Canvas for coastal tourist attractions in Balikpapan Timur District. In order to support Balikpapan Timur District to become one of the centers of tourism development in Balikpapan City, it is necessary to strengthen each tourist attraction in this area both internally and externally, including in developing its business so that it can always be innovative and can adapt to the existing competitive climate.